2016
DOI: 10.4038/cjs.v45i3.7400
|View full text |Cite
|
Sign up to set email alerts
|

The repertoire and structure of vocalizations of the Southern Magpie Robin (Copsychus saularis ceylonensis) in the Kandy region, Sri Lanka

Abstract: Bird vocalizations could be used to analyze various ecological aspects and hypotheses as the environment affects the evolution of acoustic signals. Oriental Magpie Robin (Copsychus saularis ceylonensis) is one such ideal candidate for ecological studies in Sri Lanka since it shows a wide variety of interesting behaviors including elaborative vocalizations. Yet, there has been hardly any scientific studies directed towards the vocalization activities or on the ecological aspects of this bird. Thus, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…A difference in low frequency was also observed in the morning with higher ambient noise than the evening. As compared to previous studies (Koli 2014;Wanniarachchi & Wijesundara 2016), our study showed that the low and high frequencies obtained were lower. The range of frequency of the Oriental Magpie Robin found in our study was lower, but higher in time interval between strophes than those found in Thailand (Danmek & Sitasuwan 2016).…”
Section: Modelcontrasting
confidence: 61%
See 2 more Smart Citations
“…A difference in low frequency was also observed in the morning with higher ambient noise than the evening. As compared to previous studies (Koli 2014;Wanniarachchi & Wijesundara 2016), our study showed that the low and high frequencies obtained were lower. The range of frequency of the Oriental Magpie Robin found in our study was lower, but higher in time interval between strophes than those found in Thailand (Danmek & Sitasuwan 2016).…”
Section: Modelcontrasting
confidence: 61%
“…The Oriental Magpie Robin (Copsychus saularis), locally known as Murai Kampung, is a common songbird that can be found in many open habitats (Danmek & Sitasuwan 2017;Davison & Yeap 2010;Dunmak & Sitasuwan 2007;Koli 2014;Robson 2000;Wanniarachchi & Wijesundara 2016;Wells 2010). It is very vocal in urban areas and this makes it an ideal species to examine the effects of urban environmental factors on its acoustic communication involving flexible song traits (McCarthy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…saularis is a secondary cavity nester; which both male and female build up their nests in natural cavities like tree holes and artificial cavities like nest boxes or any holes in a building (Singh, Bhatt, Sethi & Dadwal, 2016). Being classified as a territorial species, the male of C. saularis utters its territorial song to establish their own territory and attract females during mating season (Bhatt, Kumar, Singh & Payne, 2000;Catchpole & Slater, 2008;Wanniarachchi & Wijesundara, 2016). It also maintains its own territory, which is known as territoriality.…”
Section: Introductionmentioning
confidence: 99%
“…This act will occur when the male individual acts defensively toward any intruders within a specific area of which it fully uses its territorial area for nesting activities, obtaining food resources, and mating (Brown, 1964;Odum & Kuenzler, 1955). The territorial area might consist of a part or entire space used by the male individual to carry out its daily activities during mating and breeding season (Catchpole & Slater, 2008;Wanniarachchi & Wijesundara, 2016).…”
Section: Introductionmentioning
confidence: 99%